Indonesian-English Code-Switching in Contemporary Contexts: Insights from 2023–2024 Data - Akfan, Sofyan Sukwara (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2025)
Code-switching, prevalent in multilingual contexts, exemplifies linguistic adaptability and social conformity. This study employed a qualitative research design utilizing content analysis methods, involving randomly selected participants and unstructured interviews to investigate Indonesian-English code-switching on social media platforms, particularly Facebook. The data underwent evaluation in three phases: reduction, display, and conclusion formulation. The results identified three main types of code-switching: intra-sentential (50%), inter-sentential (30%), and tag-switching (20%). Intra-sentential switching was the predominant form of code-switching, indicating a high degree of integration between the two languages in informal online conversation. Individuals swap codes for various reasons: to display their status or